Empirical Analysis of Non-medical Drivers and Medical Treatment Selection - Bertoli, Paola; Cahlík, Tomáš, 1956-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
Modern health care systems struggle to reduce the burden of inappropriate treatments, which increase expenditures without improving the medical condition of patients. As a result, spending containment has become one of the most critical issues for healthcare providers and health policy, holding a central role on both the policy agenda and public debate. In the economic literature, practice styles, monetary incentives, and medical malpractice are the main factors used to explain large differences in both expenditures and use of health treatments. However, not enough consideration has been given to these factors within public health care systems, as the vast majority of existing contributions focus on the US experience. The present work contributes to the empirical study of the impact of non-medical incentives on treatment selection and the possible institutional determinants of such incentives with a specific emphasis on public health care systems. Specifically, the focus is on the role of medical malpractice and monetary incentives and how these factors interact with the institutional setting in which doctors operate. Our findings show that the provision of health care and the related providers are not immune to the strategic behaviors and doctors respond to both liability pressure and monetary incentives.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet